1993
DOI: 10.1002/mus.880161217
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of nerve conduction measurements at the carpal tunnel

Abstract: We compared the predictive values of three measurements of sensory conduction of the median nerve at the carpal tunnel (maximum latency difference [MLD], 8-cm latency [S8], and 14-cm latency [S14]) in 2334 hands of industrial workers, workers' compensation patients, and students. The MLD was determined by the centimetric technique. The MLD was the most sensitive and efficient measurement for predicting carpal tunnel syndrome (CTS). An MLD > or = 0.40 ms correctly identified 86.3% of 753 hands with CTS. The MLD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(47 citation statements)
references
References 10 publications
1
45
0
1
Order By: Relevance
“…These asymptomatic workers have mean SCV-WP values lower than Kimura's healthy people (however within the normal interval) ( Table 2) and the hypothesis could be that they represent a group of preclinical cases of CTS, although the few prospective studies report that most people with abnormal median NCSs do not develop symptoms of CTS [35,42]. Compared with the symptomatic workers with the same occupational exposure, they could also form a sort of subgroup that is more resistant to industrial biomechanical exposure (Isolani et al manuscript submitted).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…These asymptomatic workers have mean SCV-WP values lower than Kimura's healthy people (however within the normal interval) ( Table 2) and the hypothesis could be that they represent a group of preclinical cases of CTS, although the few prospective studies report that most people with abnormal median NCSs do not develop symptoms of CTS [35,42]. Compared with the symptomatic workers with the same occupational exposure, they could also form a sort of subgroup that is more resistant to industrial biomechanical exposure (Isolani et al manuscript submitted).…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, a high prevalence of median mononeuropathy was reported in asymptomatic subjects, and (other) paresthesias suggestive of CTS were reported in individuals without electrodiagnostic signs of CTS [14,21,23,35].…”
Section: Introductionmentioning
confidence: 96%
“…Among the traditional NCS parameters, we recorded discordance rates with respect to symptoms ranging from 19% for WSL to 51% for MCV-WP in the nondominant hand (and from 40% to 50%, respectively, in the dominant hand). Although most studies of occupational CTS consider only sensory parameters (Nathan et al 1993;Bingham et al 1996;Werner et al 1997;Homan et al 1999), motor NCS parameters have also been proposed as a sensitive test for CTS (Waltors and Murray 2001;Chang et al 2002). Nathan et al concluded that maximum latency difference determined by the centimetric technique described by Kimura (1979) was the most sensitive and the most reliable sensory test to confirm a clinical diagnosis of CTS, while sensory 8-cm latency could be recommended as a sensitive substitute (Nathan et al 1993).…”
Section: Discussionmentioning
confidence: 98%
“…The sensitivity and specificity of EDT for diagnosis of CTS has been estimated to be 80-90% and 82-85%, respectively. 10,13,15,25) Eventually, approximately 10 to 15% of subjects are the "milder" cases of CTS, those with clinical symptom of CTS but normal NCS results. Koyuncuoglu et al 13) found that such "milder" cases of CTS were significantly higher median nerve CSA than healthy control subjects.…”
Section: Discussionmentioning
confidence: 99%